Digital Marketing and Information Systems for Micro, Small, and Medium Enterprises (MSMEs) Empowerment and Sustainable Community Development in Sidoarjo, Indonesia - Triwiyanto, Triwiyanto; Luthfiyah, Sari; Utomo, Bedjo (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
This community service program aimed at enhancing digital marketing and information systems in Desa Balongdowo, Sidoarjo, to foster economic growth and improve access to essential services. The local economy, primarily based on seafood processing, particularly kupang products, faced limited market reach due to traditional marketing methods. Consequently, this initiative sought to empower local Micro, Small, and Medium Enterprises (MSMEs) by introducing digital marketing strategies, utilizing platforms like TikTok and e-commerce sites such as Tokopedia, Bukalapak, and Shopee. Additionally, a digital information portal was developed to centralize information regarding village activities, health services, and business opportunities. The program’s methodology included workshops and seminars on digital marketing, e-commerce, and information systems, followed by hands-on sessions for creating digital content and managing online transactions. The implementation began with training MSMEs on digital tools and website development, while also providing technical support for local entrepreneurs to establish online presences. A participatory approach was adopted, ensuring that the community was actively involved throughout the process. The results of the program were positive, with participants demonstrating significant improvements in digital marketing skills and the successful establishment of e-commerce platforms. Furthermore, the village’s information portal was launched, providing residents and outsiders with vital community updates. The program concluded with evaluations that showed increased awareness and adoption of digital tools, thereby enhancing MSME competitiveness and community welfare. In conclusion, the initiative proved effective in empowering Desa Balongdowo’s community by improving digital marketing capabilities and establishing a digital information system. Future efforts should focus on continuous training and infrastructure improvements to ensure sustainable progress